2011
DOI: 10.1007/s11249-011-9873-8
|View full text |Cite
|
Sign up to set email alerts
|

Real Time TEM Imaging of Compression and Shear of Single Fullerene-Like MoS2 Nanoparticle

Abstract: The deformation and degradation behavior of single inorganic fullerenes nanoparticles of MoS 2 under compression and shear has been observed in real time using a high-resolution transmission electron microscope equipped with a nanoindentation holder. The MoS 2 nanoparticles were compressed using a nanoindenter and a truncated diamond tip. For the first time, real time imaging of the deformation of individual nanoparticles clearly shows first orientation changes in the particle shape during loading process foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 16 publications
3
46
1
Order By: Relevance
“…As explained by Lecouvet et al [34], HNTs are hard aluminosilicates with interlayer water molecules where weak Van der Waals forces and H-bonds are present, and shearing occurs due to the slip motion between these layers, particularly for larger nanoparticle diameters (>120 nm). A similar behavior has also been reported experimentally by Lahouij et al [35] for inorganic fullerene-like (IF)-MoS 2 nanoparticles. At contact pressures of 1 GPa exfoliation of outer fullerene sheets was found to be the predominant mechanism, and at lower pressures (0.1 GPa) a rolling/sliding mechanism was observed.…”
Section: Surface Analysissupporting
confidence: 88%
“…As explained by Lecouvet et al [34], HNTs are hard aluminosilicates with interlayer water molecules where weak Van der Waals forces and H-bonds are present, and shearing occurs due to the slip motion between these layers, particularly for larger nanoparticle diameters (>120 nm). A similar behavior has also been reported experimentally by Lahouij et al [35] for inorganic fullerene-like (IF)-MoS 2 nanoparticles. At contact pressures of 1 GPa exfoliation of outer fullerene sheets was found to be the predominant mechanism, and at lower pressures (0.1 GPa) a rolling/sliding mechanism was observed.…”
Section: Surface Analysissupporting
confidence: 88%
“…Due to their good mechanical resistance they do not deform easily under the effect of the gradual increase of the pressure near the contact zone. Recently some authors [19,20] investigated in real time the deformation and degradation behaviour of the same ''well crystallised'' IF-MoS 2 nanoparticles under compression and shear stress using a high-resolution transmission electron microscope equipped with a nanoindentation holder. The authors showed that the ability of the particle to exfoliate was strongly dependent on their physical properties.…”
Section: Discussionmentioning
confidence: 99%
“…With advanced chemical techniques, MoS 2 with these novel morphologies has been synthesized [14][15][16][17][18]. The applications of spherical IF-MoS 2 [19][20][21][22] and MoS 2 nanotubes [23][24][25][26] also enrich the lubricating mechanisms of solid lubricants.…”
Section: Introductionmentioning
confidence: 99%